2022
DOI: 10.1155/2022/4347466
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lysophospholipid Supplementation in Feed with Low Protein or Lipid on Growth Performance, Lipid Metabolism, and Intestinal Flora of Largemouth Bass (Micropterus salmoides)

Abstract: The largemouth bass (Micropterus salmoides) were fed diets with three experimental feeds, a control diet (Control, crude protein (CP): 54.52%, crude lipid (CL): 11.45%), a low-protein diet with lysophospholipid (LP-Ly, CP: 52.46%, CL: 11.36%), and a low-lipid diet with lysophospholipid (LL-Ly, CP: 54.43%, CL: 10.19%), respectively. The LP-Ly and LL-Ly groups represented the addition of 1 g/kg of lysophospholipids in the low-protein and low-lipid groups, respectively. After a 64-day feeding trial, the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…In fish, Liu et al [ 27 ] reported that the response to stimulus is involved in the upregulated response to handling and confinement stress in trout, while Raposo de Magalhaes et al [ 53 ] also referred to this GO term in the analysis of the stress-responsive hepatic proteome in gilthead sea bream. In parallel, a recent study [ 54 ] in largemouth bass ( Micropterus salmoides ) demonstrated that the addition of LPLs increased the abundance of beneficial microbiota and decreased the abundance of harmful microbiota in the intestinal flora, which could also be related to the proposed less-reactive condition of fish receiving LPL supplementation. We attribute our novel results on the response to stress to a general reduced proinflammatory state in LPL-fed fish.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In fish, Liu et al [ 27 ] reported that the response to stimulus is involved in the upregulated response to handling and confinement stress in trout, while Raposo de Magalhaes et al [ 53 ] also referred to this GO term in the analysis of the stress-responsive hepatic proteome in gilthead sea bream. In parallel, a recent study [ 54 ] in largemouth bass ( Micropterus salmoides ) demonstrated that the addition of LPLs increased the abundance of beneficial microbiota and decreased the abundance of harmful microbiota in the intestinal flora, which could also be related to the proposed less-reactive condition of fish receiving LPL supplementation. We attribute our novel results on the response to stress to a general reduced proinflammatory state in LPL-fed fish.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, other upregulated DEPs occurred in several linked pathways related to protein synthesis, such as mRNA maturation, protein translation, protein location, and post-translational modifications (PTMs) of newly formed proteins. Among the 119 downregulated DEPs obtained in the intestine, only the proteins (54) clustering in "cellular component organization" (Figure 3B, PPI-enrichment p-value = 6.9 × 10 −4 ) were grouped in a subsequent interactome with relevant biological processes affected (Figure 5). For instance, there were 19 proteins clustered in the "response to stress" (GO:0006950), 7 in the "viral process" (GO:0016032), and 4 in "type I interferon signaling pathway" (GO:0060337), some of them belonging to two of these clusters and one to all.…”
Section: Effects On Enterocyte Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 400 mg/kg dietary LPLs supplementation could promote the growth performance, improve hepatic lipid metabolism, and alleviate inflammation response in juvenile large yellow croaker (Larimichthys crocea) [14]. A previous study found that supplementation with 1 g/kg LPLs in low-protein (crude protein: 52.46%, crude lipid: 11.36%) or low-lipid (crude protein, 54.43%; crude lipid, 10.19%) diets could increase the activity of intestinal digestive enzymes, enhance the hepatic lipid metabolism, promote protein deposition, and modulate the intestinal flora of largemouth bass [15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, LPL changes cell membrane permeability and expands membranous pores in intestinal cell membranes, causing a greater flux of small and large molecules of digested nutrients across the cell membrane (Lundbaek et al, 2010;Arouri and Mouritsen, 2013) and phospholipids also contribute it is rapidly degraded as part of the energy requirements of intestinal cells and reduces their damage, therefore expanding the crypts' depth as well as villi length and width, which improves intestinal health (Skoura and Hla, 2009;Boontiam et al, 2017). Solbi et al (2021) and Lu et al (2022) noted that adding rapidly decomposing phosphorous fats to the broiler diet improved the productive performance of birds. The current study sought to illustrate the impact of early feeding at varying concentrations of LPL on the phenotypic and physical traits of the hatched chicks, as well as the hatching characteristics.…”
mentioning
confidence: 99%